1971
DOI: 10.1103/physreva.3.979
|View full text |Cite
|
Sign up to set email alerts
|

Lifetimes of Metastable CO andN2Molecules

Abstract: The average lifetime of metastable CO molecules in the a II state excited by electron impact at 7. 5 eV at room temperature was found to be about 1 msec. Lifetimes of metastable N2 molecules in the a'0~and E Z~s tates were found to be 115+20 and 190 +30 @sec, respectively. There was evidence for at least one higher-lying metastable state of CO at about 10eV having a lifetime of about 0. 1 msec. The lifetimes were obtained in a time-of-flight experiment and deduced from the measurements without resorting to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

1971
1971
2010
2010

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(34 citation statements)
references
References 15 publications
3
30
1
Order By: Relevance
“…This assignment was definitely confirmed later theoretically and experimentally [34,35,[38][39][40][41]. Our calculations show that the 1 3 Σ g -is lying closely to the E state.…”
Section: Implications For the Radiative Transitions In Nsupporting
confidence: 72%
“…This assignment was definitely confirmed later theoretically and experimentally [34,35,[38][39][40][41]. Our calculations show that the 1 3 Σ g -is lying closely to the E state.…”
Section: Implications For the Radiative Transitions In Nsupporting
confidence: 72%
“…Therefore, in this work, the two-cycle RPD operation of the gun was eliminated and only the first cycle of the pulsing scheme pre- UCRL-20905 Figure 1 shows the excitation f'unctionformetastable states produced by electron impact on CO. The excitation threshold was found to be 5.9 eV as compared to the spectroscopic value of 6.01 eVe All curves recorded in this study showed the same steady rise to a plateau at approximately 10 eVe A reproducible feature was the small increase in signal near 13 eVe The shape of the curve agrees quite well with the initial portion of a metastable CO curve recently published by Borst and Zipf [3]. It is, however, quite different from the curve measured by Olmsted, Newton, and street [6].…”
supporting
confidence: 77%
“…The lowest Rydberg state with gerade symmetry is characterized by a long lifetime. The lifetime of the E 3 R g state with the electronic configuration of (N 2 + :X 2 R core)(3sr g ) was reported to be 190 ls [1]. These metastable nitrogen molecules play a very important role not only in the chemistry of high-temperature flames but also in the photochemistry of the upper stratosphere.…”
Section: Introductionmentioning
confidence: 97%